PROMOTING ENTREPRENEURIAL EDUCATION FOR ILLITERATE WOMEN FOR SOCIO-ECONOMIC DEVELOPMENT IN BALOCHISTAN - Prof. Dr. Mumtaz Ali Baloch; Bibi Sultana; Aftab Aslam (International Journal of Contemporary Issues in Social Sciences, 2024)
Balochistan, a province in Pakistan, faces significant challenges in achieving socio-economic development. One major hurdle lies in the low literacy rate, particularly among rural women. Statistics indicate that more than 70% of women in rural Balochistan lack access to education. The absence of education hinders their ability to engage in economic activities and sustains a cycle of poverty. However, a promising solution emerges in the form of entrepreneurial education. This study investigates the potential of promoting entrepreneurial education programs specifically designed for illiterate women living in rural Balochistan. By equipping these women with essential business skills, knowledge, and confidence, the research aims to demonstrate how entrepreneurial education can act as a catalyst for their socio-economic empowerment. The proposed study will adopt a participatory and culturally sensitive approach, catering to the specific needs and learning styles of uneducated women. The curriculum will focus on developing practical skills in areas such as product development, marketing, basic financial literacy, and business management. Additionally, the program will foster a supportive network by connecting women with mentors, microfinance opportunities, and access to local markets. The research will employ a mixed-methods approach using quantitative data collection through surveys and qualitative data through interviews and focus group discussions. This will allow for a comprehensive understanding of the program’s impact on the participants’ entrepreneurial knowledge, self-efficacy, and income generation. By promoting entrepreneurial education among uneducated rural women, this research strives to contribute to a more equitable and prosperous future for Balochistan. The findings will not only inform the development of effective educational programs but also highlight the transformative power of empowering women to become active economic agents.